2018
DOI: 10.1177/1557988318810243
|View full text |Cite
|
Sign up to set email alerts
|

Couvade Syndrome Among Jordanian Expectant Fathers

Abstract: Studies of different cultures have reported that expectant fathers experience physiological and psychological changes during their partner’s pregnancy. These symptoms are classed as Couvade Syndrome (sympathetic pregnancy) symptoms. The main aim of this study was to determine the prevalence of Couvade Syndrome among Jordanian expectant fathers. A descriptive quantitative research design that utilized the Men’s Health During Partners’ Pregnancy (MHDPP) questionnaire was employed to collect data from three Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
2
2
0
1
Order By: Relevance
“…The feeling of unpreparedness was the main reason behind their feeling of loss of control. This finding is in line with two previous local studies that found that new parents, both female and male, face challenges and difficulties during this critical life stage (Mrayan et al, 2016, 2019). This study also revealed that a number of different reasons were behind early marriage, associated with cultural mores or social norms and beliefs.…”
Section: Discussionsupporting
confidence: 93%
“…The feeling of unpreparedness was the main reason behind their feeling of loss of control. This finding is in line with two previous local studies that found that new parents, both female and male, face challenges and difficulties during this critical life stage (Mrayan et al, 2016, 2019). This study also revealed that a number of different reasons were behind early marriage, associated with cultural mores or social norms and beliefs.…”
Section: Discussionsupporting
confidence: 93%
“…Results similar to those presented in this paper were obtained by Ganapathy, among others, who observed the following the most common: appetite changes (82.7%), indigestion (78.5%), headaches (68.7%), insomnia (90.1%) and irritability (66.4%) [2]. Mrayan and co-authors [14], on the other hand, observed the most common symptoms in men during their study: heartburn (72.4%), fatigue (69.3%), back pain (68.0%), leg cramps (56.0%) and increased appetite (55.8%), as well as anxiety (67.4%), lowered mood (60.9%), mood swings (58.9%), and stress (58.5%).…”
Section: Syndrom Kuwady Wśród Partnerów Kobiet W Ciąży Fizjologicznej...supporting
confidence: 90%
“…Mrayan i wsp. [14] z kolei w trakcie swoich badań najczęściej obserwowali u mężczyzn: zgagę (72,4%), zmęczenie (69,3%), bóle pleców (68,0%), skurcze nóg (56,0%) oraz wzmożony apetyt (55,8%), a także niepokój (67,4%), obniżenie nastroju (60,9%), huśtawki nastroju (58,9%) oraz stres (58,5%).…”
Section: Couvade Syndrome Among Partners Of Women With Physiological ...unclassified
“…Couvade syndrome is by definition a male syndrome-the sensation by a male that he is first pregnant, then experiences labour and then suffers from postpartum depression. It is considered a sympathy syndrome, an overidentification with a female partner [60] and is characterized by symptoms of anxiety and depression [61]. Women who are not pregnant can sometimes overidentify with a pregnant woman to whom they feel close.…”
Section: Culture-bound Delusional Syndromes and Gender Differencesmentioning
confidence: 99%